Employment for individuals with Asperger syndrome or non-verbal learning disability : stories and strategies. - Fast, Yvona, ....- (London : Kingsley, 2004)
Contents:---------Most people with Non-Verbal Learning Disorder (NLD) or Asperger Syndrome(AS) are underemployed. This book sets out to change this. With practicaland technical advice on everything from job hunting to interviewtechniques, from fitting in in the workplace to whether or not todisclose a diagnosis, this book guides people with NLD or AS successfullythrough the employment field. There is also information for employers,agencies and careers counsellors on AS and NLD as invisibledisabilities, including an analysis of the typical strengths of somebodywith NLD or AS, and how to use these positively in the workplace.Practical information and lists of career resources are supported bynumerous case studies to inspire and advise. An essential resource forpeople with NLD or AS seeking or in employment and their existing orpotential employers.
Keywords: Aspergersyndroom; NLD